Satisfaction toward on agricultural extension by social media of Phokaruna Co., Ltd. in Chiang Mai province - Phokaruna, A.; Sirisunyaluck, R. (International Journal of Agricultural Technology, 2015)
This research aimed to study the situation of customers on agricultural extension exposure via social media of Phokaruna Co., Ltd. and the satisfaction of customers on agricultural extension exposure via social media of Phokaruna Co., Ltd. Samples were the customers of Phokaruna Co., Ltd. in Chiang Mai Province that visit the social media in agricultural extension services of the company in amount of 280 people. Data were collected using the questionnaires and analyzed by frequency and percent calculation. The research results revealed that 1) the customers of Phokaruna Co., Ltd. that visit the social media in agricultural extension services of the company were mostly male at the age of 41-50 years old. Besides, the level of education was mostly bachelor’s degree while the majority had job as agriculturist and the family income per month was 10,001-20,000 baht. Typically, social media using took less than 30 minutes. Overall, the main purpose of using social media was to contact with the company for inquire the details of the products. 2) In case of customer satisfaction on agricultural extension exposure via social media of Phokaruna Co., Ltd. satisfied at high level. Mostly, they were answered the agriculture problems rapidly and save cost when compared with going to find the information by themselves.